On the effective conductivity and the apparent viscosity of a thin rough polymer interface using PGD‐based separated representations. (14th July 2020) - Ammar, Amine; Ghnatios, Chady; Delplace, Frank; Barasinski, Anais; Duval, Jean‐Louis; Cueto, Elías; Chinesta, Francisco
Summary: Composite manufacturing processes usually proceed from preimpregnated preforms that are consolidated by simultaneously applying heat and pressure, so as to ensure a perfect contact compulsory for making molecular diffusion possible. However, in practice, the contact is rarely perfect. This results in a rough interface where air could remain entrapped, thus affecting the effective thermal conductivity. Moreover, the interfacial melted polymer is squeezed flowing in the rough gap created by the fibers located on the prepreg surfaces. Because of the typical dimensions of a composite prepreg, with thickness orders of magnitude smaller than its other in‐plane dimensions, and its surface roughness having a characteristic size orders of magnitude smaller than the prepreg thickness, high‐fidelity numerical simulations for elucidating the impact of surface and interface roughness remain today, despite the impressive advances in computational availabilities, unattainable. This work aims at elucidating roughness impact on heat conduction and the effective viscosity of the interfacial polymer squeeze flow by using an advanced numerical strategy able to reach resolutions never attained until now, a sort of numerical microscope able to attain the scale of the smallest geometrical detail.